PEMANFAATAN LAHAN DIBAWAH TEGAKAN DALAM UPAYA MENDUKUNG KETAHANAN PANGAN DI DUSUN BANGKO HALMAHERA BARAT - Firman Yahya; Firlawanti Lestari Baguna (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The use of land under stands is an alternative to improve the quality of land around the forest. Bangko is one of the hamlets located around the forest in West Halmahera. The Village Development activities carried out aim to enable the community to utilize the available land, especially under the stands to meet daily food needs and increase household income. The methods used in village development activities are socialization, education, and training in the community. The result of the implementation of village development is the achievement of targeted outputs in the form of community skills in cultivating land and chili cultivation techniques under the stand. So that it is expected to be able to become a production center to meet the needs of the community of Bangko